2010
DOI: 10.1177/104063871002200422
|View full text |Cite
|
Sign up to set email alerts
|

Polyomavirus Infection in a Free-Ranging California Sea Lion (Zalophus Californianus) with Intestinal T-Cell Lymphoma

Abstract: Abstract. An adult female California sea lion (Zalophus californianus) that stranded in central California was found to have a small glossal polypoid mass on gross necropsy. Histologically, the mass was consistent with a fibropapilloma, and intranuclear inclusions were found within endothelial cells lining small arterioles within the mass. Electron microscopy revealed 40-nm virions within endothelial intranuclear inclusions. Rolling circle amplification was used to obtain a partial viral genomic sequence. Sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…In avian hosts infection is often associated with acute and severe disease, while mammalian PyVs generally result in mild or subclinical infections [2] unless the host is immunosuppressed [6][9]. Significantly, our knowledge of PyV epidemiology and pathogenesis is mostly limited to terrestrial species, and the only reported marine PyV infection is in a California sea lion ( Zalophus californianus ) with small proliferative lesions on the dorsal mucosa of the tongue [10], [11]. Here we describe a novel cetacean PyV and implicate the virus in the death of a free-ranging short-beaked common dolphin ( Delphinus delphis ).…”
Section: Introductionmentioning
confidence: 99%
“…In avian hosts infection is often associated with acute and severe disease, while mammalian PyVs generally result in mild or subclinical infections [2] unless the host is immunosuppressed [6][9]. Significantly, our knowledge of PyV epidemiology and pathogenesis is mostly limited to terrestrial species, and the only reported marine PyV infection is in a California sea lion ( Zalophus californianus ) with small proliferative lesions on the dorsal mucosa of the tongue [10], [11]. Here we describe a novel cetacean PyV and implicate the virus in the death of a free-ranging short-beaked common dolphin ( Delphinus delphis ).…”
Section: Introductionmentioning
confidence: 99%
“…Among oncogenic viruses are those in the Polyomaviridae family, whose members infect an array of vertebrate species, including birds, humans, nonhuman primates, bovids, rodents, and sea lions ( 1 , 2 ). Infection in mammals typically results in persistent asymptomatic infection ( 3 , 4 ).…”
mentioning
confidence: 99%
“…Polyomaviruses also infect a wide variety of mammalian and avian hosts, including the recently described novel polyomaviruses of bats (Myotis species) (32), sea lions (Zalophus californianus) (8,47), multimammate mice (Mastomys species) (33), canaries (Serinus canaria) (19), orangutans (Pongo species) (17), squirrel monkeys (Saimiri species) (46), chimpanzees (Pan troglodytes subsp. verus) (28), and gorillas (Gorilla gorilla) (28).…”
mentioning
confidence: 99%